Early short-term infant food supplementation, maternal weight loss and duration of breast-feeding: a randomised controlled trial in rural Senegal - Ly, C.T; Diallo, A; Simondon, F; Simondon, K.B (European journal of clinical nutrition, 2006)
Objective: Early supplementation of breastfed infants may have consequences both for the mother and the child. We hypothesised that it would result in decreased maternal weight loss and in shorter durations of breastfeeding and birth intervals. Design: Controlled randomised population-based trial. Setting: Six villages in the Sine area of Senegal, West Africa. Subjects: Healthy breastfed infants and their mothers, 68 controls and 66 supplemented infants at randomization. Intervention: Supplementation with high-energy, nutrient dense food from 4 to 7 months of age, twice daily under supervision of field workers. Both controls and supplemented infants were free to eat other complementary foods. Maternal weight was measured monthly. Dates of breastfeeding cessation and of subsequent births were collected prospectively through weekly demographic surveillance, and were analysed using Cox's regression models and 'intent-to-supplement' approach. Results: Mean maternal weight gain from 4 to 7 months postpartum tended to be greater in the supplemented group (+0.25 kg/months, 95% confidence interval (CI): -0.07, +0.57). Supplemented infants were breastfed for significantly longer durations than controls (medians: 24.9 and 23.7 months, respectively, P: 0.034). Their adjusted hazard ratio (HR) for breastfeeding cessation was 0.59 (95% CI: 0.40, 0.89). Their mothers had a lower risk of a new birth than mothers of controls (adjusted HR: 0.57, 95% CI: 0.36, 0.92). Conclusions: Early short-term infant supplementation tended to decrease maternal postpartum weight loss, but it increased, rather than shortened, the duration of breastfeeding and birth interval. Sponsorship: This study was supported by a grant from the French Ministry of Research (Grant 92L0623).